Similar But Different: Integrated Phylogenetic Analysis of Austrian and Swiss HIV-1 Sequences Reveal Differences in Transmission Patterns of the Local HIV-1 Epidemics. (1st August 2022) - Kusejko, Katharina; Tschumi, Nadine; Chaudron, Sandra E.; Nguyen, Huyen; Battegay, Manuel; Bernasconi, Enos; Böni, Jürg; Huber, Michael; Calmy, Alexandra; Cavassini, Matthias; Egle, Alexander; Grabmeier-Pfistershammer, Katharina; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: Phylogenetic analyses of 2 or more countries allow to detect differences in transmission dynamics of local HIV-1 epidemics beyond differences in demographic characteristics. Methods: A maximum-likelihood phylogenetic tree was built using pol -sequences of the Swiss HIV Cohort Study (SHCS) and the Austrian HIV Cohort Study (AHIVCOS), with international background sequences. Three types of phylogenetic cherries (clusters of size 2) were analyzed further: (1) domestic cherries; (2) international cherries; and (3) SHCS/AHIVCOS-cherries. Transmission group and ethnicities observed within the cherries were compared with the respective distribution expected from a random distribution of patients on the phylogeny. Results: The demographic characteristics of the AHIVCOS (included patients: 3′141) and the SHCS (included patients: 12′902) are very similar. In the AHIVCOS, 36.5% of the patients were in domestic cherries, 8.3% in international cherries, and 7.0% in SHCS/AHIVCOS cherries. Similarly, in the SHCS, 43.0% of the patients were in domestic cherries, 8.2% in international cherries, and 1.7% in SHCS/AHIVCOS cherries. Although international cherries in the SHCS were dominated by heterosexuals with men who have sex with men being underrepresented, the opposite was the case for the AHIVCOS. In both cohorts, cherries with one patient belonging to the transmission group intravenous drug user and the other one non–intravenous drug user were underrepresented. Conclusions: In both cohorts, international HIV transmission plays a major role in the local epidemics, mostly driven by men who have sex with men in the AHIVOS, and by heterosexuals in the SHCS, highlighting the importance of international collaborations to understand global HIV transmission links on the way to eliminate HIV.